Understanding conformational dynamics of complex lipid mixtures relevant to biology - Friedman, Ran; Khalid, Syma; Aponte-Santamaria, Camilo; Arutyunova, Elena; Becker, Marlon; Boyd, Kevin J.; Christensen, Mikkel; Coimbra, Joao T. S.; Concilio, Simona; Daday, Csaba; van Eerden, Floris J.; Fernandes, Pedro A.; et al. (Journal of membrane biology, 2018)
This is a perspective article entitled "Frontiers in computational biophysics: understanding conformational dynamics of complex lipid mixtures relevant to biology" which is following a CECAM meeting with the same name.

Dioxolanone-anchored poly(allyl ether)-based cross-linked dual-salt polymer electrolytes for high-voltage lithium metal batteries - Vijayakumar, Vidyanand; Diddens, Diddo; Heuer, Andreas; Kurungot, Sreekumar; Winter, Martin; Nair, Jijeesh Ravi (ACS Applied Materials & Interfaces, 2020)
Novel cross-linked polymer electrolytes (XPEs) are synthesized by free-radical copolymerization induced by ultraviolet (UV)-light irradiation of a reactive solution, which is composed of a difunctional poly(ethylene glycol) diallyl ether oligomer (PEGDAE), a monofunctional reactive diluent 4-vinyl-1,3-dioxolan-2-one (VEC), and a stock solution containing lithium salt (lithium bis(trifluoromethanesulfonyl)imide, LiTFSI) in a carbonate-free nonvolatile plasticizer, poly(ethylene glycol) dimethyl ether (PEGDME). The resulting polymer matrix can be represented as a linear polyethylene chain functionalized with cyclic carbonate (dioxolanone) moieties and cross-linked by ethylene oxide units. A series of XPEs are prepared by varying the [O]/[Li] ratio (24 to 3) of the stock solution and thoroughly characterized using physicochemical (thermogravimetric analysis-mass spectrometry, differential scanning calorimetry, NMR, etc.) and electrochemical techniques. In addition, quantum chemical calculations are performed to elucidate the correlation between the electrochemical oxidation potential and the lithium ion-ethylene oxide coordination in the stock solution. Later, lithium bis(fluorosulfonyl)imide (LiFSI) salt is incorporated into the electrolyte system to produce a dual-salt XPE that exhibits improved electrochemical performance, a stable interface against lithium metal, and enhanced physical and chemical characteristics to be employed against high-voltage cathodes. The XPE membranes demonstrated excellent resistance against lithium dendrite growth even after reversibly plating and stripping lithium ions for more than 1000 h with a total capacity of 0.5 mAh cm(-2). Finally, the XPE films are assembled in a lab-scale lithium metal battery configuration by using carbon-coated LiFePO4 (LFP) or LiNi0.8Co0.15Al0.05O2 (NCA) as a cathode and galvanostatically cycled at 20, 40, and 60 degrees C. Remarkably, at 20 degrees C, the NCA-based lithium metal cells displayed excellent cycling stability and good capacity retention (>50%) even after 1000 cycles.
Keywords: cross-linked polymer electrolyte; dual-salt electrolyte; high-voltage cathode; lithium metal battery; solvent-free photopolymerization